Awareness of blood pressure status, undiagnosed hypertension and proteinuria among adults in Umuahia, South-East Nigeria - Chimezie Godswill Okwuonu (Sahel Medical Journal, 2016)
Background: Hypertension and proteinuria are risk factors for cardiovascular disease. They are also important risk factors for further deterioration of renal function in chronic kidney disease (CKD) irrespective of the cause of CKD. Both are asymptomatic at early stages and can only be detected during medical consultation for a related or unrelated illness. Materials and Methods: This was a cross-sectional study carried out to assess awareness of blood pressure (BP) status among adults in a semi-urban community in Southern Nigeria. The magnitude of undiagnosed hypertension and proteinuria in the community was also assessed. BP measurement was by standardized method while proteinuria was detected by use of urinary dipstick. Data was analyzed using SPSS version 21.0. Results: A total of 389 people were recruited. There were 223 (57.3%) males and 116 (42.7%) females. Only 104 (26.7%) were aware of their BP status before the study. Awareness was higher in females but did not differ significantly among the different age groups, educational status or occupations. Hypertension was newly diagnosed in 105 (27%) of the participants while proteinuria was diagnosed in 47 (12.1%). Proteinuria and overweight were higher among participants with prehypertension than other BP categories. Conclusions: The study revealed a low level of awareness of BP status and a high prevalence of undiagnosed hypertension and proteinuria in the community. Concerted efforts are needed to improve the awareness of BP and other risk factors for cardiovascular and kidney diseases.